Training on making sausages from durian seed flour as a business opportunity in Pulliwa Village, Sulawesi Barat Province [Pelatihan pembuatan sosis dari tepung biji durian sebagai potensi usaha di Desa Pulliwa, Provinsi Sulawesi Barat] - Mukhlisah, Andi Nurul; Syah, Setiawan Putra; Ningtiyas, Weny Dwi; Irfan, Muhammad; Rahmawati, Rahmawati (Buletin Pengabdian Bulletin of Community Services, 2025)
Sausage is a processed product made from chicken or beef obtained from a mixture of finely ground meat and flour with added seasonings and food additives that are stuffed into casings. The filling ingredient commonly used in sausage production is tapioca flour. One alternative to tapioca flour is durian seed flour. Durian seed flour can be used as a filling ingredient in processed chicken products because it contains 88.68% starch. The addition of durian seed flour is one alternative that can be used to increase sausage variety and improve sausage quality. The method used to solve the problem was an institutional approach, namely a process of continuous guidance and assistance throughout the activity. There were 20 participants involved in this activity, consisting of women from the Paraita Women Farmers Group (KWT). The assistance was focused on guiding and assisting the KWT women in applying the technology of processing livestock products in the form of sausages. The community service activity was carried out by conducting counseling, followed by training and mentoring for the women of KWT in Pulliwa Village, Bulo District, Polewali Mandar Regency. This activity provided information to KWT that sausage can be made not only with tapioca flour, but also with cheaper durian seed flour, thus opening up business opportunities to increase members' income. The community service activity through counseling, training, and mentoring for the women of the Paraita Women Farmers Group (KWT) in Pulliwa Village, Bulo District, Polewali Mandar Regency successfully increased the knowledge and skills of the participants in processing livestock products into sausage products with the innovation of adding durian seed flour as a filler.